2016
DOI: 10.2174/1568026616666160216155927
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-Mediated Inhibition of Metal Binding to the Multi-Metal Site on Serum Albumin: Implications for Cardiovascular Disease

Abstract: (2016) Fatty acid-mediated inhibition of metal binding to the multi-metal site on serum albumin : implications for cardiovascular disease. Current Trends in Medicinal Chemistry, 16. Permanent WRAP URL:http://wrap.warwick.ac.uk/78963 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 137 publications
(221 reference statements)
0
23
0
Order By: Relevance
“…In this way, the recruitment of platelets to sites of injury such as tumours and wounds, followed by their activation, generates a Zn 2+ -rich microenvironment 92 . This has implications for angiogenesis 15 in malignant tumours 93 and physiological haemostasis 29 , 30 , 94 , 95 . In both processes, Zn 2+ binding to HRG, or some of its histidine-rich derivatives, increases the affinity to poly-anionic biomolecules, specifically heparin and cell surface-bound heparan sulfate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the recruitment of platelets to sites of injury such as tumours and wounds, followed by their activation, generates a Zn 2+ -rich microenvironment 92 . This has implications for angiogenesis 15 in malignant tumours 93 and physiological haemostasis 29 , 30 , 94 , 95 . In both processes, Zn 2+ binding to HRG, or some of its histidine-rich derivatives, increases the affinity to poly-anionic biomolecules, specifically heparin and cell surface-bound heparan sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Haemostasis, the first step in wound healing, is dynamically regulated by Zn 2+ 29 , again with platelets as central players. Several lines of evidence indicate that HRG is a central part of this dynamic regulation 30 , 94 , 95 . Zinc-mediated HRG-heparin interactions promote blood clotting, as they decrease anti-coagulatory heparin/anti-thrombin complex formation 29 .…”
Section: Discussionmentioning
confidence: 99%
“…178 Thus, FFA binding alters conformational changes and inhibits the metal ion binding to albumin. 179,180 Chronic diseases associated with ''glycated/ oxidized'' albumin, oxidative stress generates ''irreversible'' oxidation-modified albumin secondary to oxidation adducts on albumin. 176 Henceforth, the use of both standard ACB assay and ELISA tests for determining IMA levels is ideal.…”
Section: St2mentioning
confidence: 99%
“…37,49 studied in depth using X-ray crystallography, 37,42,43 molecular modelling, NMR spectroscopy, 44 and isothermal titration calorimetry, 41,45 and is now well-understood in chemical model systems. 46 Interdependence of Zn 2+ and FFA binding is due to the proximal location of the primary Zn 2+ binding site (site A) and one (out of three; 47 Fig. 1b) high affinity fatty acid binding site (FA2), both situated at the interface of domains I and II of albumin.…”
Section: Introductionmentioning
confidence: 99%
“…47 As a result of this finding, it has been suggested that fluctuations in the levels of FFAs in the blood may impact zinc speciation, with several downstream effects predicted. 14,46,48 Although cellular zinc uptake and compartmentalisation is largely governed by membrane-bound transporters of the ZIP and ZnT families, 50,51 it is conceivable that plasma speciation could impact the uptake of Zn 2+ by endothelial cells and blood cells, including leukocytes involved in immune function. 13 In this regard, the effects of zinc on immune cells are of high relevance, since zinc is required for both innate and adaptive immune response, modulating cytokine secretion, 52 and playing roles in T cell maturation 53 and B cell response to vaccination.…”
Section: Introductionmentioning
confidence: 99%